PENERAPAN MODEL GAME BASED LEARNING EDUCAPLAY PADA PEMBELAJARAN IPA SISWA KELAS V SD NEGERI DURIAN TERUNG - Lau Langga Wuni Az, Reva; Erwandi, Rudi; Krisnawati, Yuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the completeness of science learning outcomes of fifth grade students of Durian Terung State Elementary School after the application of the Game Based Learning model assisted by Educaplay media. This study uses a Quantitative method with a pre-experimental design of the One Group Pretest-Posttest Design type. The population in this study were all fifth grade students of Durian Terung State Elementary School in the 2024/2025 academic year totaling 29 students. The sampling technique used Random Sampling with a lottery method, and the sample was class VA with 20 students. The data collection technique was carried out through a learning outcome test in the form of multiple choice questions given twice, namely pre-test and post-test. Data analysis techniques with the following steps: normality test and t-test. Based on the data analysis, the results of the initial test (Pre-test) were known with an average value of 49,70 and the average value of the final test (Post-test) was 71.70. This shows that the average value of the final test (Post-test) is greater than the initial test (Pre-test). After being calculated with the t-test, the value of (2.37) was obtained which was compared with the value of with a significance level of 5% or 0.05 was (1.73). So the value of  ≥  or 2.22 ≥ 1.73 so that  is rejected and  is accepted. So it can be concluded that the results of learning science of grade V students of Durian Terung Elementary School after the implementation of the Educaplay Game Based Learning model are significantly complete.